10.1159/000503210 (Inactive DOIs, 2000)
Background The traditional deep sedation approach has been linked to prolonged ventilation, increased delirium incidence, and long-term cognitive impairment. Modern evidence now supports lighter sedation protocols with daily interruptions and spontaneous breathing trials. Summary The authors explore the pathophysiology of sedation-related complications including delirium, ventilator-induced diaphragmatic dysfunction, and ICU-acquired weakness. They analyze clinical assessment tools ranging from validated scales to emerging objective monitoring technologies (processed electroencephalography, automated pupillometry). The pharmacological discussion contrasts traditional benzodiazepines with newer alternatives (propofol, dexmedetomidine, remifentanil) that show improved outcomes regarding delirium, ventilation duration, and cognitive function. Critical examination of sedation-ventilator mode interactions and comparison of analgosedation versus traditional sedation-first paradigms addresses unresolved clinical questions in integrating these therapeutic domains. Structured approaches including goal-oriented protocols and the ABCDEF bundle are presented as implementation frameworks. The review highlights non-pharmacologic interventions as essential complements to drug therapy: sleep promotion, early mobilization, family engagement, and environmental modifications. Special consideration is given to unique populations requiring tailored approaches, including geriatric, neurologic, cardiac, and COVID-19 patients. Key messages The authors conclude by addressing future directions in sedation practice, emphasizing cost-effectiveness analysis, quality improvement initiatives, and research priorities that will guide the next phase of sedation management in mechanical ventilation.